STAGES IN THE DEVELOPMENT OF DIGITAL IMAGES: STAGES IN THE DEVELOPMENT OF DIGITAL IMAGES - Peneva, Velichka; Stoykov, Evgeni (JOURNAL SCIENTIFIC AND APPLIED RESEARCH, 2025)
Digital imaging is a key part of modern technology, finding application in almost every sphere of human activity – from medicine and science to the arts and communications. This technological process is part of the broader evolution of digitalization, which is going through significant stages of development based on innovations in computing technologies and optoelectronic systems.